A new libelluloid dragonfly from late Paleocene deposits in Argentina (Odonata: Italoansida) - Julián F. PETRULEVIČIUS; André NEL (European Journal of Entomology, 2002)
A new genus and species of "libelluloid" dragonfly, Jujusia maizgorda gen. n., sp. n., of the clade Italoansida Bechly, 1996, from the late Paleocene, Maíz Gordo Formation, north-western Argentina, is described. Its phylogenetic relationships within the clade Cavilabiata Bechly, 1996 are discussed.